1996
DOI: 10.1128/aac.40.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and resistance studies of AG1343, an orally bioavailable inhibitor of human immunodeficiency virus protease

Abstract: AG1343 ([3S-(3R*,4aR*,8aR*,2'S*,3'S*)]-2-[2' hydroxy-3'-phenylthiomethyl-4'-aza-5'-oxo-5'-(2''-methyl-3''-hydro xy-phenyl) pentyl]-decahydroiso-quinoline-3-N-t-butylcarboxamide methanesulfonic acid) is a selective, nonpeptidic inhibitor of human immunodeficiency virus (HIV) protease (Ki = 2 nM) that was discovered by protein structure-based drug design methodologies. AG1343 was effective against the replication of several laboratory and clinical HIV type 1 (HIV-1) or HIV-2 isolates including pyridinone- and zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(105 citation statements)
references
References 34 publications
(52 reference statements)
4
100
1
Order By: Relevance
“…Nine PR inhibitors (PIs) have been approved by the Food and Drug Administration (FDA). [4][5][6][7][8][9][10][11][12] Nevertheless, the currently available PIs were developed and tested only against subtype B PRs. Some studies have shown that non-subtype B viruses show different responses than the responses of subtype B virus Abbreviations used: HIV-1, human immunodeficiency virus type 1; PR, protease; PI, protease inhibitor; NFV, nelfinavir; FDA, Food and Drug Administration; WT, wild-type; MD, molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Nine PR inhibitors (PIs) have been approved by the Food and Drug Administration (FDA). [4][5][6][7][8][9][10][11][12] Nevertheless, the currently available PIs were developed and tested only against subtype B PRs. Some studies have shown that non-subtype B viruses show different responses than the responses of subtype B virus Abbreviations used: HIV-1, human immunodeficiency virus type 1; PR, protease; PI, protease inhibitor; NFV, nelfinavir; FDA, Food and Drug Administration; WT, wild-type; MD, molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, PIs resembled NRTIs and NNRTIs. However, initial single amino acid mutations resulted in a modest change (less than a factor of 5) in drug sensitivity in vitro [76][77][78][79] yet, secondary mutations lead to high-level drug resistance and considerable cross-resistance to other protease inhibitors [75,80,81]. This was mirrored in vivo when two PIs did not protect against HIV-1 burden in PI-experienced patients [75,80,81].…”
Section: We Have (A) Haart!mentioning
confidence: 98%
“…Therefore, HIV-1 PR is an attractive target for anti-HIV-1 drugs. Today, nine protease inhibitors [6][7][8][9][10][11][12][13][14] have been approved by the FDA and have successfully lowered the death rate owing to AIDS in developed countries during the past decade. However, the currently available protease inhibitors were developed and tested only against subtype B PRs, and HIV-1 frequently acquires the resistance to these inhibitors through specific mutations due to the high polymorphism and adaptability of the protease [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%